RANCANG BANGUN MEDIA PEMBELAJARAN PENGENALAN PERANGKAT LUNAK UNTUK SISWA SEKOLAH DASAR - Setiyorini, Agustin (Informasi Interaktif, 2020)
The introduction of computers in elementary schools is deemed necessary because, along with technological advances in the present, children must begin to be introduced to terms in computers. Software or what is often called software is one part of the computer. Learning media is a way for children in elementary schools to learn about software. Learning media has a very important role in education and training activities. Learning media that are used can help facilitate learning effectively and efficiently. The purpose of this research is to design a software learning media for elementary school children as a basic introduction to the software itself. In this study using Macromedia Flash 8 software and using the Research and Development (R&D) method, while the development model uses ADDIE.Key words: software, media, learning.